The gender gap in fisheries and climate policy: Insights from Southeast Asia - Danielle Robinson; Tyas Ismi Trialfhianty; Ben Charo; Helen E. Fox; Alice Joan Ferrer; Maria Beger (Marine Policy, 2026)

Ridge-to-reef conservation avoids future deforestation and sediment exposure of coral reefs - Dominic Muenzel; Eleanor Stewart; Noviar Andayani; Alex J. Dumbrell; Jamaluddin Jompa; Gino Limmon; Jatna Supriatna; Johny S. Tasirin; Nurul L. Winarni; Zuliyanto Zakaria; Zoe G. Davies; Matthew J. Struebig; et al. (Biological Conservation, 2026)

Multi-decadal resilience (2002–2023) of subtropical coral communities in the Solitary Islands, eastern Australia, despite severe cumulative disturbances - Hamish A. Malcolm; Marine Lechene; Renata Ferrari; Curtis Champion; Steven J. Dalton; Maria Beger; James Cant; Fiona Chong; Wanchien Victoria Hsiao; Sun W. Kim; Liam Lachs; Stephen D. A. Smith; et al. (Coral Reefs, 2026)

Two decades of coral monitoring reveal thermal stress thresholds on Indonesian reefs - Tries B. Razak; Cut Aja Gita Alisa; Muhammad Abrar; Rizya Ardiwijaya; Imam Bachtiar; Ravienkha R. Budaya; Dan Exton; Giyanto; Aradea R. Hakim; Muhammad Erdi Lazuardi; M. Munasik; Efin Muttaqin; et al. (Biological Conservation, 2026)

Subtropical specialists dominate a coral range expansion front - Fiona Chong; Giun Yee Soong; Agus Alim Hakim; Camille Burke; Stéphane De Palmas; Fabian Gösser; Wanchien Victoria Hsiao; Hiroki Kise; Miyuki Nishijima; Akira Iguchi; Brigitte Sommer; Domino Joyce; et al. (Coral Reefs, 2026)
Potential range expansion of scleractinian corals in high-latitude reefs is critically dependent on the coral host-symbiont relationship that determines coral growth and survival. Although increases in coral cover have been observed at higher latitudes, the identities of habitat-building reef corals and their symbionts are underreported. Here, we examine how scleractinian host and symbiont Symbiodiniaceae diversity changes along a tropical–temperate environmental gradient. We use Pocillopora spp. and associated symbiont communities as a model to understand whether they are expanding their range poleward and the role of symbionts in this process. Along the Kuroshio Current, which carries warm equatorial waters northward along the Pacific coast of Japan, we collected coral tissues from 23 (sub)tropical-to-temperate reefs, from southern Iriomote in the Ryukyu Islands (24°N) to northernmost Kushimoto on mainland Japan (33°N). We examined host identities through direct sequencing of the mitochondrial open reading frame (mtORF) and symbiont identities with next-generation sequencing of the internal transcribed spacer 2 (ITS2) region of the ribosomal DNA. Our results show a dramatic reduction of Pocillopora haplotypes and a marked change in dominant symbiont types northward (poleward) from Cape Sata (30°N), Kagoshima. ‘Tropical’ Pocillopora haplotypes were absent from mainland Japan sites. We also demonstrate high host specificity between the subtropical Pocillopora haplotype and Cladocopium symbiont types. Our findings question how common ‘coral tropicalisation’ is, and the location of the coral range expansion front. The specificity of hosts and symbionts in high-latitude corals suggests that high-latitude reefs are unlikely to support the persistence of tropical zooxanthellate corals.

Multi-scale observations during the 2024 mass coral bleaching event on Heron Reef, Australia - Devin A. Rowell; Nicholas M. Hammerman; Kirsten M. Golding; Tania Marie Kenyon; Zoe Meziere; Courtney Morgans; Kristen Taylor Brown; Faye F. Diederiks; David E. Carrasco Rivera; Karen Eigeland; Roima Paewai-Huggins; Kathryn Markey; et al. (Marine Biology, 2026)

Optimising site selection for ecosystem approaches to shrimp aquaculture in mangrove systems - Dominic Muenzel; Aji W. Anggoro; Dewi Embong Bulan; Yadi; Nurfadilah; Rahadian Pratama; Muhammad Ilman; Basir; Mariski Nirwan; Vabian Adriano; Muhammad M. Bayyan; Topik Hidayat; et al. (Aquaculture International, 2025)
Indonesia has experienced significant mangrove loss due to aquaculture expansion, particularly for shrimp farming, leading to the degradation of habitats and critical ecosystem services such as carbon storage, coastal protection, and fish spawning grounds. Ecosystem based aquaculture approaches offer a pathway to both mitigate environmental impacts and support sustainable seafood production. Here we explore the implementation of the Shrimp-Carbon Aquaculture (SECURE) approach in Berau Regency, East Kalimantan, Indonesia, which integrates mangrove restoration with organic shrimp farming to achieve sustainable aquaculture. Using environmental DNA (eDNA) metabarcoding to detect species from DNA shed into the environment, we assessed impacts of SECURE intervention compared to traditional ponds and found increased abundance of key taxonomic groups associated with healthy aquatic ecosystems, such as phytoplankton Chaetoceros, Chlorophyceae, and Cryptomonadales and zooplankton Calanoida and Cyclopoida. We then conducted a spatial prioritisation analysis to identify additional areas for SECURE implementation, considering mangrove restoration and protection potential, profitability, and intervention costs. High-priority ponds for restoration were typically set back from riverbanks, large, and spatially clustered, indicating opportunities for cost-effective, strategic expansion. This study underscores how spatial prioritisation can support strategic implementation of aquaculture to balance ecosystem-based aquaculture development with environmental conservation, offering a replicable framework for other regions facing similar challenges. This approach provides a pathway for achieving long-term sustainability in aquaculture, contributing to global food security and ecological resilience.

Toxicity of Melaleuca rhaphiophylla essential oils against Sitophilus zeamais and Sitophilus oryzae - Rubens Candido Zimmermann; Ana Marta Schafaschek; Adélia Maria Bischoff; Matheus Beger; Julia Sant’ana; Sofia Bin de Macedo; Milena Ielen; Carlos Eduardo Nogueira Martins; Sarah da Costa Amaral; Rilton Alves de Freitas; Alessandra Benatto; Carolina Gracia Poitevin; et al. (Journal of Pest Science, 2025)

A corallimorpharian barren in southwestern Kochi, Japan - James Davis Reimer; Fabian Gösser; Kenta C. F. Kondo; Stephane De Palmas; Daito Yamaguchi; Maria Beger; Brigitte Sommer; Fiona Chong; Camille Burke; Ayaka Umeda Paul; James Lock; Takuma Mezaki (Marine Biodiversity, 2025)

Inferring Species Interactions From Co‐occurrence Networks With Environmental DNA Metabarcoding Data in a Coastal Marine Food Web - Elizabeth Boyse; Kevin P. Robinson; Ian M. Carr; Elena Valsecchi; Maria Beger; Simon J. Goodman (Molecular Ecology, 2025)
A good understanding of biotic interactions is necessary to accurately predict the vulnerability of ecosystems to climate change. Recently, co‐occurrence networks built from environmental DNA (eDNA) metabarcoding data have arisen as a tool to explore interspecific interactions in ecological communities exposed to different human and environmental pressures. Such networks can identify environmentally driven relationships in microbial and eukaryotic communities, but whether inferred co‐occurrences robustly represent biotic interactions remains unclear. Here, we tackle this challenge and compare spatio‐temporal variability in the structure and complexity of inferred co‐occurrence networks and food webs, using 60 eDNA samples covering vertebrates and other eukaryotes in a North Sea coastal ecosystem. We compare topological characteristics and identify highly connected species across spatial and temporal subsets to evaluate variance in community composition and structure. We find consistent trends in topological characteristics across eDNA‐derived co‐occurrence networks and food webs that support some ability for the co‐occurrence networks to detect real ecological processes, despite trophic interactions forming a minority of significant co‐occurrences. The lack of significant trophic interactions detected in co‐occurrence networks may result from ecological complexities, such as generalist predators having flexible interactions or behavioural partitioning, the inability to distinguish age class with eDNA or co‐occurrences being driven by non‐trophic or abiotic interactions. We find support for using eDNA‐derived co‐occurrence networks to infer ecological interactions, but further work is needed to assess their power to reliably detect and differentiate different interaction types and overcome methodological limitations, such as species detection uncertainties, which could influence inferred ecosystem complexity.

Engaging customary law to improve the effectiveness of marine protected areas in Indonesia - Tyas Ismi Trialfhianty; Claire Helen Quinn; Maria Beger (Ocean & Coastal Management, 2025)

Present distribution of common hippopotamus populations in southern Africa, and the need for a centralised database - Hannah Lacy; Maria Beger; Lochran W. Traill (Biological Conservation, 2025)

Does high parasite load contribute to limitation of the poleward range of Acropora corals? - Brigitte Sommer; Yuen Y. Chang; Maria Beger; John M. Pandolfi (Coral Reefs, 2024)
The role of species interactions in setting species range limits is rarely empirically explored. Here, we quantify host and parasite densities in subtropical eastern Australia (26.65°–30.20°S) to examine whether parasitism might contribute to range limitation of Acropora corals at their cold-range boundary. 79% of Acropora corals had endolithic barnacles (family Pyrgomatidae), with higher parasite load in larger corals and up to 141 barnacles per coral. Parasite load increased poleward and closer to the mainland and was greater in cooler and high nutrient environments. Parasite burden was higher at sites with fewer Acropora corals, broadly consistent with the hypothesis that parasites can fragment host populations where host densities are low, and the parasite is a better disperser than the host. Whilst the mechanism is unclear, our findings suggest that at the high densities recorded here, coral-barnacles could influence range dynamics of Acropora corals at their poleward range limit.

Variation in species and functional composition of octocorals and zoantharians across a tropical to temperate environmental gradient in the Indo-Pacific - Nori Otis; James D. Reimer; Iori Kawamura; Hiroki Kise; Masaru Mizuyama; Masami Obuchi; Brigitte Sommer; Catherine S. McFadden; Maria Beger (Coral Reefs, 2024)
Global warming causes functional shifts and reorganisation in marine communities through range shifts to high-latitude reefs and cnidarian bleaching mortality in the tropics. Such changes threaten the integrity and structure of marine communities, especially as foundational and associated species are reduced or lost. However, comparatively little is known about the extent of range shifts and their ecological consequences for the overlooked components of marine ecosystems, such as octocorals and zoantharians (O + Z) on shallow coral reefs. As these groups play a crucial part in building complexity and sustaining life in reef communities, functional shifts in these taxa may cascade through the entire ecosystem, but these processes have not been quantified. Here, we examined the environmental drivers and functional consequences of spatial variation in octocoral and zoantharian communities across 27 sites in southern Japan, spanning from tropical to warm-temperate waters. We collated a trait database for 42 entities (species, genus, and family level identifications) of octocorals and zoantharians and calculated functional diversity and functional richness to measure functional compositional change. We identified five functional groups according to their trait similarities and identified how their abundances respond to changing environmental factors with general additive models (GAMs). We found functional shifts among octocorals and zoantharians across the tropical to temperate thermal gradient, with the abundances of two functional groups best explained by gradients in minimum sea surface temperature. Non-linear relationships between the functional groups and thermal gradients imply a more intricate relationship than expected, suggesting other non-temperature-based drivers, e.g., nitrogen or pH levels might also play an important role. Only functional group richness and species richness showed significant correlations with latitude, whilst functional diversity and functional richness did not. Our results indicate that octocoral and zoantharian communities and functionality potentially undergo shifts with clear community compositional changes, influenced by climate change across environmental gradients. However, the taxonomy and identification of these taxa remain difficult, and information on functional traits is often sparse or not species-specific, indicating a clear need for further basic zoological and ecological work on octocorals and zoantharians.

Variation in functional composition of reef fishes along a tropical‐to‐temperate gradient - Charlotte G. Clay; James D. Reimer; Brigitte Sommer; Katie M. Cook; Masaru Mizuyama; Masami Obuchi; Iori Kawamura; Hiroki Kise; Maria Beger (Journal of Biogeography, 2024)
Aims Transformation of species and functional composition on subtropical reefs are ongoing due to poleward range shifts of some tropical species, with largely unknown consequences to ecosystem functioning. Trait‐based approaches are powerful tools to quantify such changes. Here, we evaluated changes in the trait composition of coral‐associated fish assemblages along a tropical‐to‐temperate environmental gradient of ca. 1400 km in southern Japan with abundance‐weighted trait expression to assess how trait composition changes with increasing latitude. Location Ryukyu Islands and southern Pacific coast of Japan. Taxon Reef fish. Methods We tested for shifts in trait space and functional redundancy, based on five morphological, life history and behavioural traits: maximum length, pelagic larval duration, trophic level, substrate preference and reproductive mode. Our trait database was coded with two approaches, first, by attributing a single value to each trait per species, and second, by fuzzy coding that allows more than one value per trait and hence considers some intraspecific trait variation. Results We found a reduction in specialist habitat traits (coral substrate preference, nesters and herbivores) and an increase in generalist traits (predators) with increasing latitude, along with a contraction in trait space from tropical‐to‐temperate reefs. Functional redundancy declined with increasing latitude. These trends were closely linked with latitudinal gradients in temperature, along with changes in other environmental factors such as turbidity and photosynthetically active radiation. Main Conclusion Functional turnover and contractions are thus likely due to the marginal conditions for coral‐associated fishes at higher latitudes, favouring generalist species, whereas increased resources at lower latitudes favour high redundancy and niche partitioning. Accounting for intraspecific trait variation indicated the same trends but highlighted increased functional vulnerability across all sites. We show that trait complexity in coral‐associated fish communities decreases from tropical‐to‐temperate reefs, highlighting the reduced functional scope that comes with marginal environmental conditions.

Diversification of refugia types needed to secure the future of coral reefs subject to climate change - Tim R. McClanahan; Emily S. Darling; Maria Beger; Helen E. Fox; Hedley S. Grantham; Stacy D. Jupiter; Cheryl A. Logan; Elizabeth Mcleod; Lisa C. McManus; Remy M. Oddenyo; Gautam S. Surya; Amelia. S. Wenger; et al. (Conservation Biology, 2024)
Identifying locations of refugia from the thermal stresses of climate change for coral reefs and better managing them is one of the key recommendations for climate change adaptation. We review and summarize approximately 30 years of applied research focused on identifying climate refugia to prioritize the conservation actions for coral reefs under rapid climate change. We found that currently proposed climate refugia and the locations predicted to avoid future coral losses are highly reliant on excess heat metrics, such as degree heating weeks. However, many existing alternative environmental, ecological, and life‐history variables could be used to identify other types of refugia that lead to the desired diversified portfolio for coral reef conservation. To improve conservation priorities for coral reefs, there is a need to evaluate and validate the predictions of climate refugia with long‐term field data on coral abundance, diversity, and functioning. There is also the need to identify and safeguard locations displaying resistance toprolonged exposure to heat waves and the ability to recover quickly after thermal exposure. We recommend using more metrics to identify a portfolio of potential refugia sites for coral reefs that can avoid, resist, and recover from exposure to high ocean temperatures and the consequences of climate change, thereby shifting past efforts focused on avoidance to a diversified risk‐spreading portfolio that can be used to improve strategic coral reef conservation in a rapidly warming climate.

Integrating environmental, evolutionary, and socioeconomic vulnerability to future-proof coastal conservation planning - Erica S. Nielsen; Maria Beger; Romina Henriques; Sophie von der Heyden (Biological Conservation, 2023)

Coral assemblages at higher latitudes favor short‐term potential over long‐term performance - James Cant; James D. Reimer; Brigitte Sommer; Katie M. Cook; Sun W. Kim; Carrie A. Sims; Takuma Mezaki; Cliodhna O'Flaherty; Maxime Brooks; Hamish A. Malcolm; John M. Pandolfi; Roberto Salguero‐Gómez; et al. (Ecology, 2023)
The persistent exposure of coral assemblages to more variable abiotic regimes is assumed to augment their resilience to future climatic variability. Yet, while the determinants of coral population resilience across species remain unknown, we are unable to predict the winners and losers across reef ecosystems exposed to increasingly variable conditions. Using annual surveys of 3171 coral individuals across Australia and Japan (2016–2019), we explore spatial variation across the short‐ and long‐term dynamics of competitive, stress‐tolerant, and weedy assemblages to evaluate how abiotic variability mediates the structural composition of coral assemblages. We illustrate how, by promoting short‐term potential over long‐term performance, coral assemblages can reduce their vulnerability to stochastic environments. However, compared to stress‐tolerant, and weedy assemblages, competitive coral taxa display a reduced capacity for elevating their short‐term potential. Accordingly, future climatic shifts threaten the structural complexity of coral assemblages in variable environments, emulating the degradation expected across global tropical reefs.

Regional and global climate risks for reef corals: Incorporating species‐specific vulnerability and exposure to climate hazards - Sun W. Kim; Brigitte Sommer; Maria Beger; John M. Pandolfi (Global Change Biology, 2023)
Climate change is driving rapid and widespread erosion of the environmental conditions that formerly supported species persistence. Existing projections of climate change typically focus on forecasts of acute environmental anomalies and global extinction risks. The current projections also frequently consider all species within a broad taxonomic group together without differentiating species‐specific patterns. Consequently, we still know little about the explicit dimensions of climate risk (i.e., species‐specific vulnerability, exposure and hazard) that are vital for predicting future biodiversity responses (e.g., adaptation, migration) and developing management and conservation strategies. Here, we use reef corals as model organisms ( n = 741 species) to project the extent of regional and global climate risks of marine organisms into the future. We characterise species‐specific vulnerability based on the global geographic range and historical environmental conditions (1900–1994) of each coral species within their ranges, and quantify the projected exposure to climate hazard beyond the historical conditions as climate risk. We show that many coral species will experience a complete loss of pre‐modern climate analogs at the regional scale and across their entire distributional ranges, and such exposure to hazardous conditions are predicted to pose substantial regional and global climate risks to reef corals. Although high‐latitude regions may provide climate refugia for some tropical corals until the mid‐21st century, they will not become a universal haven for all corals. Notably, high‐latitude specialists and species with small geographic ranges remain particularly vulnerable as they tend to possess limited capacities to avoid climate risks (e.g., via adaptive and migratory responses). Predicted climate risks are amplified substantially under the SSP5‐8.5 compared with the SSP1‐2.6 scenario, highlighting the need for stringent emission controls. Our projections of both regional and global climate risks offer unique opportunities to facilitate climate action at spatial scales relevant to conservation and management.

Recent exposure to environmental stochasticity does not determine the demographic resilience of natural populations - James Cant; Pol Capdevila; Maria Beger; Roberto Salguero‐Gómez (Ecology Letters, 2023)
Escalating climatic and anthropogenic pressures expose ecosystems worldwide to increasingly stochastic environments. Yet, our ability to forecast the responses of natural populations to this increased environmental stochasticity is impeded by a limited understanding of how exposure to stochastic environments shapes demographic resilience. Here, we test the association between local environmental stochasticity and the resilience attributes (e.g. resistance, recovery) of 2242 natural populations across 369 animal and plant species. Contrary to the assumption that past exposure to frequent environmental shifts confers a greater ability to cope with current and future global change, we illustrate how recent environmental stochasticity regimes from the past 50 years do not predict the inherent resistance or recovery potential of natural populations. Instead, demographic resilience is strongly predicted by the phylogenetic relatedness among species, with survival and developmental investments shaping their responses to environmental stochasticity. Accordingly, our findings suggest that demographic resilience is a consequence of evolutionary processes and/or deep‐time environmental regimes, rather than recent‐past experiences.

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Integrating larval connectivity into the marine conservation decision‐making process across spatial scales - Dominic Muenzel; Kay Critchell; Courtney Cox; Stuart J. Campbell; Raymond Jakub; Wahid Suherfian; La Sara; Iliana Chollett; Eric A. Treml; Maria Beger (Conservation Biology, 2023)
Larval dispersal connectivity is typically integrated into spatial conservation decisions at regional or national scales, but implementing agencies struggle with translating these methods to local scales. We used larval dispersal connectivity at regional (hundreds of kilometers) and local (tens of kilometers) scales to aid in design of networks of no‐take reserves in Southeast Sulawesi, Indonesia. We used Marxan with Connectivity informed by biophysical larval dispersal models and remotely sensed coral reef habitat data to design marine reserve networks for 4 commercially important reef species across the region. We complemented regional spatial prioritization with decision trees that combined network‐based connectivity metrics and habitat quality to design reserve boundaries locally. Decision trees were used in consensus‐based workshops with stakeholders to qualitatively assess site desirability, and Marxan was used to identify areas for subsequent network expansion. Priority areas for protection and expected benefits differed among species, with little overlap in reserve network solutions. Because reef quality varied considerably across reefs, we suggest reef degradation must inform the interpretation of larval dispersal patterns and the conservation benefits achievable from protecting reefs. Our methods can be readily applied by conservation practitioners, in this region and elsewhere, to integrate connectivity data across multiple spatial scales.

Co-variation of fish and coral traits in relation to habitat type and fishery status - Louise Anderson; Matthew McLean; Peter Houk; Curtis Graham; Kriskitina Kanemoto; Elizabeth Terk; Elizabeth McLeod; Maria Beger (Coral Reefs, 2023)
Escalating climate impacts on coral reefs are increasingly expanding management goals beyond preserving biodiversity to also maintaining ecosystem functions. Morphological and ecological species traits can help assess changes within reef communities beyond taxonomic identities alone. However, our limited understanding of trait interactions between habitat-building corals and associated reef fishes and whether they are captured by current monitoring practices hampers management. Here, we apply co-inertia analyses to test whether trait assemblages in corals and fishes co-vary across different habitats and test whether different components of the reef fish community (fisheries vs. non-target species) display distinct relationships. We find that spatial co-variation across habitat types between coral and fish traits is strengthened by the addition of non-target fishes. Additionally, even in fisheries with diverse targets, non-target species make unique contributions to the overall trait structure and highlight the importance of considering monitoring protocols when drawing conclusions about traits and ecosystems.

Comparing spatial conservation prioritization methods with site‐ versus spatial dependency‐based connectivity - Dominic Muenzel; Kay Critchell; Courtney Cox; Stuart J. Campbell; Raymond Jakub; Iliana Chollett; Nils Krueck; Daniel Holstein; Eric A. Treml; Maria Beger (Conservation Biology, 2023)
Larval dispersal is an important component of marine reserve networks. Two conceptually different approaches to incorporate dispersal connectivity into spatial planning of these networks exist, and it is an open question as to when either is most appropriate. Candidate reserve sites can be selected individually based on local properties of connectivity or on a spatial dependency‐based approach of selecting clusters of strongly connected habitat patches. The first acts on individual sites, whereas the second acts on linked pairs of sites. We used a combination of larval dispersal simulations representing different seascapes and case studies of biophysical larval dispersal models in the Coral Triangle region and the province of Southeast Sulawesi, Indonesia, to compare the performance of these 2 methods in the spatial planning software Marxan. We explored the reserve design performance implications of different dispersal distances and patterns based on the equilibrium settlement of larvae in protected and unprotected areas. We further assessed different assumptions about metapopulation contributions from unprotected areas, including the case of 100% depletion and more moderate scenarios. The spatial dependency method was suitable when dispersal was limited, a high proportion of the area of interest was substantially degraded, or the target amount of habitat protected was low. Conversely, when subpopulations were well connected, the 100% depletion was relaxed, or more habitat was protected, protecting individual sites with high scores in metrics of connectivity was a better strategy. Spatial dependency methods generally produced more spatially clustered solutions with more benefits inside than outside reserves compared with site‐based methods. Therefore, spatial dependency methods potentially provide better results for ecological persistence objectives over enhancing fisheries objectives, and vice versa. Different spatial prioritization methods of using connectivity are appropriate for different contexts, depending on dispersal characteristics, unprotected area contributions, habitat protection targets, and specific management objectives. Comparación entre los métodos de priorización de la conservación espacial con sitio y la conectividad espacial basada en la dependencia

Molecular ecology meets systematic conservation planning - Erica S. Nielsen; Jeffrey O. Hanson; Silvia B. Carvalho; Maria Beger; Romina Henriques; Francine Kershaw; Sophie von der Heyden (Trends in Ecology & Evolution, 2023)

Correction to: Transient demographic approaches can drastically expand the toolbox of coral reef science - James Cant; Roberto Salguero-Gómez; Maria Beger (Coral Reefs, 2022)

Transient demographic approaches can drastically expand the toolbox of coral reef science - James Cant; Roberto Salguero-Gómez; Maria Beger (Coral Reefs, 2022)
Coral communities are threatened by an increasing plethora of abiotic and biotic disturbances. Preventing the ensuing loss of coral coverage and diversity calls for a mechanistic understanding of resilience across coral species and populations that is currently lacking in coral reef science. Assessments into the dynamics of coral populations typically focus on their long-term (i.e. asymptotic ) characteristics, tacitly assuming stable environments in which populations can attain their long-term characteristics. Instead, we argue that greater focus is needed on investigating the transient ( i.e. short-term) dynamics of coral populations to describe and predict their characteristics and trajectories within unstable environments. Applying transient demographic approaches to evaluating and forecasting the responses of coral populations to disturbance holds promise for expediting our capacity to predict and manage the resilience of coral populations, species, and communities.

Planning for resilience: Incorporating scenario and model uncertainty and trade‐offs when prioritizing management of climate refugia - Iliana Chollett; Ximena Escovar‐Fadul; Steven R. Schill; Aldo Croquer; Adele M. Dixon; Maria Beger; Elizabeth Shaver; Valerie Pietsch McNulty; Nicholas H. Wolff (Global Change Biology, 2022)
Climate change has become the greatest threat to the world's ecosystems. Locating and managing areas that contribute to the survival of key species under climate change is critical for the persistence of ecosystems in the future. Here, we identify ‘Climate Priority’ sites as coral reefs exposed to relatively low levels of climate stress that will be more likely to persist in the future. We present the first analysis of uncertainty in climate change scenarios and models, along with multiple objectives, in a marine spatial planning exercise and offer a comprehensive approach to incorporating uncertainty and trade‐offs in any ecosystem. We first described each site using environmental characteristics that are associated with a higher chance of persistence (larval connectivity, hurricane influence, and acute and chronic temperature conditions in the past and the future). Future temperature increases were assessed using downscaled data under four different climate scenarios (SSP1 2.6, SSP2 4.5, SSP3 7.0 and SSP5 8.5) and 57 model runs. We then prioritized sites for intervention (conservation, improved management or restoration) using robust decision‐making approaches that select sites that will have a benign climate under most climate scenarios and models. The modelling work is novel because it solves two important issues. (1) It considers trade‐offs between multiple planning objectives explicitly through Pareto analyses and (2) It makes use of all the uncertainty around future climate change. Priority intervention sites identified by the model were verified and refined through local stakeholder engagement including assessments of local threats, ecological conditions and government priorities. The workflow is presented for the Insular Caribbean and Florida, and at the national level for Cuba, Jamaica, Dominican Republic and Haiti. Our approach allows managers to consider uncertainty and multiple objectives for climate‐smart spatial management in coral reefs or any ecosystem across the globe.

Life history mediates the trade‐offs among different components of demographic resilience - Pol Capdevila; Iain Stott; James Cant; Maria Beger; Gwilym Rowlands; Molly Grace; Roberto Salguero‐Gómez (Ecology Letters, 2022)
Accelerating rates of biodiversity loss underscore the need to understand how species achieve resilience—the ability to resist and recover from a/biotic disturbances. Yet, the factors determining the resilience of species remain poorly understood, due to disagreements on its definition and the lack of large‐scale analyses. Here, we investigate how the life history of 910 natural populations of animals and plants predicts their intrinsic ability to be resilient. We show that demographic resilience can be achieved through different combinations of compensation, resistance and recovery after a disturbance. We demonstrate that these resilience components are highly correlated with life history traits related to the species’ pace of life and reproductive strategy. Species with longer generation times require longer recovery times post‐disturbance, whilst those with greater reproductive capacity have greater resistance and compensation. Our findings highlight the key role of life history traits to understand species resilience, improving our ability to predict how natural populations cope with disturbance regimes.

Trait groups as management entities in a complex, multispecies reef fishery - Louise Anderson; Peter Houk; Mark G. R. Miller; Javier Cuetos‐Bueno; Curtis Graham; Kriskitina Kanemoto; Elizabeth Terk; Elizabeth McLeod; Maria Beger (Conservation Biology, 2022)
Localized stressors compound the ongoing climate‐driven decline of coral reefs, requiring natural resource managers to work with rapidly shifting paradigms. Trait‐based adaptive management (TBAM) is a new framework to help address changing conditions by choosing and implementing management actions specific to species groups that share key traits, vulnerabilities, and management responses. In TBAM maintenance of functioning ecosystems is balanced with provisioning for human subsistence and livelihoods. We first identified trait‐based groups of food fish in a Pacific coral reef with hierarchical clustering. Positing that trait‐based groups performing comparable functions respond similarly to both stressors and management actions, we ascertained biophysical and socioeconomic drivers of trait‐group biomass and evaluated their vulnerabilities with generalized additive models. Clustering identified 7 trait groups from 131 species. Groups responded to different drivers and displayed divergent vulnerabilities; human activities emerged as important predictors of community structuring. Biomass of small, solitary reef‐associated species increased with distance from key fishing ports, and large, solitary piscivores exhibited a decline in biomass with distance from a port. Group biomass also varied in response to different habitat types, the presence or absence of reported dynamite fishing activity, and exposure to wave energy. The differential vulnerabilities of trait groups revealed how the community structure of food fishes is driven by different aspects of resource use and habitat. This inherent variability in the responses of trait‐based groups presents opportunities to apply selective TBAM strategies for complex, multispecies fisheries. This approach can be widely adjusted to suit local contexts and priorities.

The role of herbivores in shaping subtropical coral communities in warming oceans - Karolina Magdalena Zarzyczny; Katie Margaret Watson; Clare Elizabeth Verduyn; James Davis Reimer; Takuma Mezaki; Maria Beger (Marine Biology, 2022)
Tropicalization is rapidly restructuring subtropical marine communities. A key driver for tropicalization is changes in herbivory pressure that are linked with degrading ecosystem stability. Consequently, subtropical algal beds are being displaced by climate-mediated colonisation of coral communities. This process is thought to be aided by the elevated herbivory resulting from tropicalization, but the relative contribution to herbivory by different taxa is not fully understood. Evaluating herbivory pressure and its effect on coral cover and rugosity across a subtropical latitudinal gradient will help predict how these processes may change with further tropicalization and ocean warming. Herbivory pressure exerted by fishes and urchins across this subtropical latitudinal gradient remains unquantified. Using in-situ feeding observations, we quantify fish and urchin herbivory pressure at seven sites across non-accreting coral communities, and warmer accreting coral reefs in southern Japan. We then relate herbivory pressure to respective fish and urchin community structure and coral cover and rugosity. Urchin herbivory is greater on non-accreting coral communities than on true coral accreting reefs; a result which is reversed for fish herbivory. Overall, herbivory pressure is greater on accreting coral reefs than on coral non-accreting communities, but is dependent on reef characteristics as community structures differ more strongly among reefs than between regions. These factors are linked to coral cover and rugosity that differ between reefs, but not between climatic regions, further emphasising the influence of local factors on the benthic cover and the associated fish and urchin community, and thus herbivory pressure. Our findings provide a foundation for understanding how non-accreting coral communities may respond to ongoing tropicalization, given the fish and invertebrate herbivores they host.

Neither historical climate nor contemporary range fully explain the extant patterns of molecular diversity in marine species - Erica S. Nielsen; Maria Beger; Romina Henriques; Sophie von der Heyden (Journal of Biogeography, 2021)
Aim Intraspecific diversity is a significant component of adaptive potential, and thus, it is important to identify the evolutionary processes that have and will continue to shape the molecular diversity of natural populations. This study aims to untangle the possible drivers of intraspecific molecular diversity by testing whether patterns of historical climatic stability or contemporary range position correlate with molecular diversity. Location South African coastline. Taxa The cape urchin ( Parechinus angulosus ), common shore crab ( Cyclograpsus punctatus ) and granular limpet ( Scutellastra granularis ). Methods Species distributions were hindcasted to the Last Glacial Maximum to assess the biogeography of the study species. Linear models were built to compare the relationships between historical climatic stability or contemporary distributional ranges with extant genetic (mtDNA) and genomic (SNP) diversity. Results We found large differences in the historical ranges among species and time periods. Regions of higher habitat stability corresponded to regions of higher molecular diversity, but historical climatic variability was not a predictor of molecular diversity within linear models. Lower genetic diversity values, and higher genetic differentiation, were detected in edge populations, but this was not consistent across marker type or species. Main conclusions Both historical and contemporary processes are potentially driving patterns of diversity, but a large portion of the variation in molecular diversity remains unexplained. Our findings suggest that marine species within cool‐temperate bioregions in the Southern Hemisphere may have more complex biogeographic and evolutionary histories than terrestrial taxa and/or coastal species within northern, formerly glaciated regions.

Distinct interspecific and intraspecific vulnerability of coastal species to global change - Erica S. Nielsen; Romina Henriques; Maria Beger; Sophie von der Heyden (Global Change Biology, 2021)
Characterising and predicting species responses to anthropogenic global change is one of the key challenges in contemporary ecology and conservation. The sensitivity of marine species to climate change is increasingly being described with forecasted species distributions, yet these rarely account for population level processes such as genomic variation and local adaptation. This study compares inter‐ and intraspecific patterns of biological composition to determine how vulnerability to climate change, and its environmental drivers, vary across species and populations. We compare species trajectories for three ecologically important southern African marine invertebrates at two time points in the future, both at the species level, with correlative species distribution models, and at the population level, with gradient forest models. Reported range shifts are species‐specific and include both predicted range gains and losses. Forecasted species responses to climate change are strongly influenced by changes in a suite of environmental variables, from sea surface salinity and sea surface temperature, to minimum air temperature. Our results further suggest a mismatch between future habitat suitability (where species can remain in their ecological niche) and genomic vulnerability (where populations retain their genomic composition), highlighting the inter‐ and intraspecific variability in species’ sensitivity to global change. Overall, this study demonstrates the importance of considering species and population level climatic vulnerability when proactively managing coastal marine ecosystems in the Anthropocene.

Linking population size structure, heat stress and bleaching responses in a subtropical endemic coral - Liam Lachs; Brigitte Sommer; James Cant; Jessica M. Hodge; Hamish A. Malcolm; John M. Pandolfi; Maria Beger (Coral Reefs, 2021)
Anthropocene coral reefs are faced with increasingly severe marine heatwaves and mass coral bleaching mortality events. The ensuing demographic changes to coral assemblages can have long-term impacts on reef community organisation. Thus, understanding the dynamics of subtropical scleractinian coral populations is essential to predict their recovery or extinction post-disturbance. Here we present a 10-yr demographic assessment of a subtropical endemic coral, Pocillopora aliciae (Schmidt-Roach et al. in Zootaxa 3626:576–582, 2013) from the Solitary Islands Marine Park, eastern Australia, paired with long-term temperature records. These coral populations are regularly affected by storms, undergo seasonal thermal variability, and are increasingly impacted by severe marine heatwaves. We examined the demographic processes governing the persistence of these populations using inference from size-frequency distributions based on log-transformed planar area measurements of 7196 coral colonies. Specifically, the size-frequency distribution mean, coefficient of variation, skewness, kurtosis, and coral density were applied to describe population dynamics. Generalised Linear Mixed Effects Models were used to determine temporal trends and test demographic responses to heat stress. Temporal variation in size-frequency distributions revealed various population processes, from recruitment pulses and cohort growth, to bleaching impacts and temperature dependencies. Sporadic recruitment pulses likely support population persistence, illustrated in 2010 by strong positively skewed size-frequency distributions and the highest density of juvenile corals measured during the study. Increasing mean colony size over the following 6 yr indicates further cohort growth of these recruits. Severe heat stress in 2016 resulted in mass bleaching mortality and a 51% decline in coral density. Moderate heat stress in the following years was associated with suppressed P. aliciae recruitment and a lack of early recovery, marked by an exponential decrease of juvenile density (i.e. recruitment) with increasing heat stress. Here, population reliance on sporadic recruitment and susceptibility to heat stress underpin the vulnerability of subtropical coral assemblages to climate change.

Importance of species translocations under rapid climate change - Nathalie Butt; Alienor L.M. Chauvenet; Vanessa M. Adams; Maria Beger; Rachael V. Gallagher; Danielle F. Shanahan; Michelle Ward; James E.M. Watson; Hugh P. Possingham (Conservation Biology, 2021)
Species that cannot adapt or keep pace with a changing climate are likely to need human intervention to shift to more suitable climates. While hundreds of articles mention using translocation as a climate‐change adaptation tool, in practice, assisted migration as a conservation action remains rare, especially for animals. This is likely due to concern over introducing species to places where they may become invasive. However, there are other barriers to consider, such as time‐frame mismatch, sociopolitical, knowledge and uncertainty barriers to conservationists adopting assisted migration as a go‐to strategy. We recommend the following to advance assisted migration as a conservation tool: attempt assisted migrations at small scales, translocate species with little invasion risk, adopt robust monitoring protocols that trigger an active response, and promote political and public support.

Functional diversity of reef molluscs along a tropical-to-temperate gradient - Matthew Floyd; Masaru Mizuyama; Masami Obuchi; Brigitte Sommer; Mark GR Miller; Iori Kawamura; Hiroki Kise; James D. Reimer; Maria Beger (Coral Reefs, 2020)
Global warming is leading to range shifts of marine species, threatening the structure and functioning of ecological communities and human populations that rely on them. The largest changes are seen in biogeographic transition zones, such as subtropical reef communities, where species range shifts are already causing substantial community reorganisation. This causes functional changes in communities over subtropical latitudes, though a baseline functional understanding remains elusive for many taxa. One key marine taxon are molluscs, which provide many ecosystem services, are important prey for fishes and are also fisheries targets themselves, but remain largely unstudied. Here, we examine the trait composition, functional diversity, and functional redundancy of mollusc assemblages along the tropical-to-temperate transition in Japan (25° to 35° Northern latitude). Specifically, we use a trait database of 88 mollusc species from 31 subtropical reefs along the Pacific coast of Japan to show that trait composition of mollusc assemblages changes continuously along the latitudinal gradient. We discover that functional diversity of mollusc assemblages decreases with increasing latitude, a pattern associated with declines in functional dispersion. Moreover, we find a clear distinction between tropical and subtropical mollusc assemblages, with substrate-attached, suspension feeding bivalves more abundant in the tropics and free-living gastropod grazers more prevalent at higher latitudes. Our trait-based evidence in this study shows a contraction and almost complete shift in the functioning of marine mollusc assemblages at biogeographic transition zones and our trait database facilitates further study. Our findings provide evidence of the changing taxonomic and functional composition of extant mollusc communities with latitude, pointing to potential pertinent changes and tropicalisation of these communities with rapid ocean warming.

Refugia under threat: Mass bleaching of coral assemblages in high‐latitude eastern Australia - Sun W. Kim; Eugenia M. Sampayo; Brigitte Sommer; Carrie A. Sims; Maria del C. Gómez‐Cabrera; Steve J. Dalton; Maria Beger; Hamish A. Malcolm; Renata Ferrari; Nicola Fraser; Will F. Figueira; Stephen D. A. Smith; et al. (Global Change Biology, 2019)
Environmental anomalies that trigger adverse physiological responses and mortality are occurring with increasing frequency due to climate change. At species' range peripheries, environmental anomalies are particularly concerning because species often exist at their environmental tolerance limits and may not be able to migrate to escape unfavourable conditions. Here, we investigated the bleaching response and mortality of 14 coral genera across high‐latitude eastern Australia during a global heat stress event in 2016. We evaluated whether the severity of assemblage‐scale and genus‐level bleaching responses was associated with cumulative heat stress and/or local environmental history, including long‐term mean temperatures during the hottest month of each year (SST LTMAX ), and annual fluctuations in water temperature (SST VAR ) and solar irradiance (PARZ VAR ). The most severely‐bleached genera included species that were either endemic to the region ( Pocillopora aliciae ) or rare in the tropics (e.g. Porites heronensis ). Pocillopora spp., in particular, showed high rates of immediate mortality. Bleaching severity of Pocillopora was high where SST LTMAX was low or PARZ VAR was high, whereas bleaching severity of Porites was directly associated with cumulative heat stress. While many tropical Acropora species are extremely vulnerable to bleaching, the Acropora species common at high latitudes, such as A. glauca and A. solitaryensis , showed little incidence of bleaching and immediate mortality. Two other regionally‐abundant genera, Goniastrea and Turbinaria , were also largely unaffected by the thermal anomaly. The severity of assemblage‐scale bleaching responses was poorly explained by the environmental parameters we examined. Instead, the severity of assemblage‐scale bleaching was associated with local differences in species abundance and taxon‐specific bleaching responses. The marked taxonomic disparity in bleaching severity, coupled with high mortality of high‐latitude endemics, point to climate‐driven simplification of assemblage structures and progressive homogenisation of reef functions at these high‐latitude locations.

The molecular biogeography of the Indo‐Pacific: Testing hypotheses with multispecies genetic patterns - Eric D. Crandall; Cynthia Riginos; Chris E. Bird; Libby Liggins; Eric Treml; Maria Beger; Paul H. Barber; Sean R. Connolly; Peter F. Cowman; Joseph D. DiBattista; Jeff A. Eble; Sharon F. Magnuson; et al. (Global Ecology and Biogeography, 2019)
Aim To test hypothesized biogeographic partitions of the tropical Indo‐Pacific Ocean with phylogeographic data from 56 taxa, and to evaluate the strength and nature of barriers emerging from this test. Location The Indo‐Pacific Ocean. Time period Pliocene through the Holocene. Major taxa studied Fifty‐six marine species. Methods We tested eight biogeographic hypotheses for partitioning of the Indo‐Pacific using a novel modification to analysis of molecular variance. Putative barriers to gene flow emerging from this analysis were evaluated for pairwise Φ ST , and these Φ ST distributions were compared to distributions from randomized datasets and simple coalescent simulations of vicariance arising from the Last Glacial Maximum. We then weighed the relative contribution of distance versus environmental or geographic barriers to pairwise Φ ST with a distance‐based redundancy analysis (dbRDA). Results We observed a diversity of outcomes, although the majority of species fit a few broad biogeographic regions. Repeated coalescent simulation of a simple vicariance model yielded a wide distribution of pairwise Φ ST that was very similar to empirical distributions observed across five putative barriers to gene flow. Three of these barriers had median Φ ST that were significantly larger than random expectation. Only 21 of 52 species analysed with dbRDA rejected the null model. Among these, 15 had overwater distance as a significant predictor of pairwise Φ ST , while 11 were significant for geographic or environmental barriers other than distance. Main conclusions Although there is support for three previously described barriers, phylogeographic discordance in the Indo‐Pacific Ocean indicates incongruity between processes shaping the distributions of diversity at the species and population levels. Among the many possible causes of this incongruity, genetic drift provides the most compelling explanation: given massive effective population sizes of Indo‐Pacific species, even hard vicariance for tens of thousands of years can yield Φ ST values that range from 0 to nearly 0.5.

Correction to: A theory for ecological survey methods to map individual distributions - Nao Takashina; Maria Beger; Buntarou Kusumoto; Suren Rathnayake; Hugh P. Possingham (Theoretical Ecology, 2018)

Revisiting “Success” and “Failure” of Marine Protected Areas: A Conservation Scientist Perspective - Sylvaine Giakoumi; Jennifer McGowan; Morena Mills; Maria Beger; Rodrigo H. Bustamante; Anthony Charles; Patrick Christie; Matthew Fox; Pablo Garcia-Borboroglu; Stefan Gelcich; Paolo Guidetti; Peter Mackelworth; et al. (Frontiers in Marine Science, 2018)

Correction to: Ocean zoning within a sparing versus sharing framework - Jennifer McGowan; Michael Bode; Matthew H. Holden; Katrina Davis; Nils C. Krueck; Maria Beger; Katherine L. Yates; Hugh P. Possingham (Theoretical Ecology, 2018)

Ocean zoning within a sparing versus sharing framework - Jennifer McGowan; Michael Bode; Matthew H. Holden; Katrina Davis; Nils C. Krueck; Maria Beger; Katherine L. Yates; Hugh P. Possingham (Theoretical Ecology, 2018)

A theory for ecological survey methods to map individual distributions - Nao Takashina; Maria Beger; Buntarou Kusumoto; Suren Rathnayake; Hugh P. Possingham (Theoretical Ecology, 2018)

Designing connected marine reserves in the face of global warming - Jorge G. Álvarez‐Romero; Adrián Munguía‐Vega; Maria Beger; Maria del Mar Mancha‐Cisneros; Alvin N. Suárez‐Castillo; Georgina G. Gurney; Robert L. Pressey; Leah R. Gerber; Hem Nalini Morzaria‐Luna; Héctor Reyes‐Bonilla; Vanessa M. Adams; Melanie Kolb; et al. (Global Change Biology, 2018)
Marine reserves are widely used to protect species important for conservation and fisheries and to help maintain ecological processes that sustain their populations, including recruitment and dispersal. Achieving these goals requires well‐connected networks of marine reserves that maximize larval connectivity, thus allowing exchanges between populations and recolonization after local disturbances. However, global warming can disrupt connectivity by shortening potential dispersal pathways through changes in larval physiology. These changes can compromise the performance of marine reserve networks, thus requiring adjusting their design to account for ocean warming. To date, empirical approaches to marine prioritization have not considered larval connectivity as affected by global warming. Here, we develop a framework for designing marine reserve networks that integrates graph theory and changes in larval connectivity due to potential reductions in planktonic larval duration ( PLD ) associated with ocean warming, given current socioeconomic constraints. Using the Gulf of California as case study, we assess the benefits and costs of adjusting networks to account for connectivity, with and without ocean warming. We compare reserve networks designed to achieve representation of species and ecosystems with networks designed to also maximize connectivity under current and future ocean‐warming scenarios. Our results indicate that current larval connectivity could be reduced significantly under ocean warming because of shortened PLD s. Given the potential changes in connectivity, we show that our graph‐theoretical approach based on centrality (eigenvector and distance‐weighted fragmentation) of habitat patches can help design better‐connected marine reserve networks for the future with equivalent costs. We found that maintaining dispersal connectivity incidentally through representation‐only reserve design is unlikely, particularly in regions with strong asymmetric patterns of dispersal connectivity. Our results support previous studies suggesting that, given potential reductions in PLD due to ocean warming, future marine reserve networks would require more and/or larger reserves in closer proximity to maintain larval connectivity.

Multispecies genetic objectives in spatial conservation planning - Erica S. Nielsen; Maria Beger; Romina Henriques; Kimberly A. Selkoe; Sophie von der Heyden (Conservation Biology, 2017)
Growing threats to biodiversity and global alteration of habitats and species distributions make it increasingly necessary to consider evolutionary patterns in conservation decision making. Yet, there is no clear‐cut guidance on how genetic features can be incorporated into conservation‐planning processes, despite multiple molecular markers and several genetic metrics for each marker type to choose from. Genetic patterns differ between species, but the potential tradeoffs among genetic objectives for multiple species in conservation planning are currently understudied. We compared spatial conservation prioritizations derived from 2 metrics of genetic diversity (nucleotide and haplotype diversity) and 2 metrics of genetic isolation (private haplotypes and local genetic differentiation) in mitochondrial DNA of 5 marine species. We compared outcomes of conservation plans based only on habitat representation with plans based on genetic data and habitat representation. Fewer priority areas were selected for conservation plans based solely on habitat representation than on plans that included habitat and genetic data. All 4 genetic metrics selected approximately similar conservation‐priority areas, which is likely a result of prioritizing genetic patterns across a genetically diverse array of species. Largely, our results suggest that multispecies genetic conservation objectives are vital to creating protected‐area networks that appropriately preserve community‐level evolutionary patterns.

The value of migration information for conservation prioritization of sea turtles in the Mediterranean - Tessa Mazor; Maria Beger; Jennifer McGowan; Hugh P. Possingham; Salit Kark (Global Ecology and Biogeography, 2016)
Aim Conservation plans often struggle to account for connectivity in spatial prioritization approaches for the protection of migratory species. Protection of such species is challenging because their movements may be uncertain and variable, span vast distances, cross international borders and traverse land and sea habitats. Often we are faced with small samples of information from various sources and the collection of additional data can be costly and time‐consuming. Therefore it is important to evaluate what degree of spatial information provides sufficient results for directing management actions. Here we develop and evaluate an approach that incorporates habitat and movement information to advance the conservation of migratory species. We test our approach using information on threatened loggerhead sea turtles ( C aretta caretta ) in the M editerranean. Location The M editerranean S ea. Methods We use Marxan, a spatially explicit decision support tool, to select priority conservation areas. Four approaches with increasing amounts of information about the loggerhead sea turtle are compared, ranging from (1) the broad distribution, (2) multiple habitat types that represent foraging, nesting and inter‐nesting habitats, (3) mark–recapture movement information to (4) telemetry‐derived migration tracks. Results We find that spatial priorities for sea turtle conservation are sensitive to the information used in the prioritization process. Setting conservation targets for migration tracks altered the location of conservation priorities, indicating that conservation plans designed without such data would miss important sea turtle habitat. We discover that even a small number of tracks make a significant contribution to a spatial conservation plan if those tracks are substantially different. Main conclusions This study presents a novel approach to improving spatial prioritization for conserving migratory species. We propose that future telemetry studies tailor their efforts towards conservation prioritization needs, meaning that spatially dispersed samples rather than just large numbers should be obtained. This work highlights the valuable information that telemetry research contributes to the conservation of migratory species.

Trait‐mediated environmental filtering drives assembly at biogeographic transition zones - Brigitte Sommer; Peter L. Harrison; Maria Beger; John M. Pandolfi (Ecology, 2014)
Abiotic filtering is a major driver of gradients in the structure and functioning of ecosystems from the tropics to the poles. It is thus likely that environmental filtering is an important assembly process at the transition of biogeographical zones where many species occur at their range limits. Shifts in species abundances and association patterns along environmental gradients can be indicative of environmental filtering, which is predicted to be stronger in areas of high abiotic stress and to promote increased similarity of ecological characteristics among co‐occurring species. Here we test these hypotheses for scleractinian corals along a broad latitudinal gradient in high‐latitude eastern Australia, where corals occur at the margins of their ranges and environmental tolerances. We quantify variation in taxonomic, zoogeographic, and functional patterns combined with null model approaches and demonstrate systematic spatial variation in community structure and significant covariance of species abundance distributions and functional characteristics along the latitudinal gradient. We describe a strong biogeographic transition zone, consistent with patterns expected under abiotic filtering, whereby species are sorted along the latitudinal gradient according to their tolerances for marginal reef conditions. High‐latitude coastal reefs are typified by widely distributed, generalist, stress‐tolerant coral species with massive and horizontally spreading morphologies and by diminishing influence of tropical taxa at higher latitudes and closer to the mainland. Higher degree of ecological similarity among co‐occurring species than expected by chance supports the environmental filtering hypothesis. Among individual traits, the structural traits corallite size and colony morphology were filtered most strongly, suggesting that characteristics linked to energy acquisition and physical stability may be particularly important for coral survival in high‐latitude environments. These findings highlight interspecific differences and species interactions with the environment as key drivers of community organization in biogeographic transition zones and support the hypothesis that environmental filters play a stronger role than biotic interactions in structuring ecological communities in areas of high abiotic stress.

Habitat partitioning and vulnerability of sharks in the Great Barrier Reef Marine Park - Daniela M. Ceccarelli; Ashley J. Frisch; Nicholas A. J. Graham; Anthony M. Ayling; Maria Beger (Reviews in Fish Biology and Fisheries, 2014)

Effectiveness of Surrogate Taxa in the Design of Coral Reef Reserve Systems in the Indo‐Pacific - MARIA BEGER; SHEILA A. McKENNA; HUGH P POSSINGHAM (Conservation Biology, 2007)
Implementing systematically designed reserve systems is crucial to slowing the global decline of coral reef health and diversity. Yet, the paucity of spatial data for most coral reef taxa often requires conservation planners to design reserve systems based only on a subset of taxonomic groups as surrogates for all other taxa. In terrestrial systems the validity of surrogates for reserve design is established by testing for cross‐taxon congruence (similarities in spatial patterns of species richness), but this concept has rarely been examined in the marine environment. We tested the suitability of taxa as conservation representation surrogates of coral reef species richness across the Indo‐Pacific, based on species lists of fishes, corals, and mollusks from 167 sites. First, we tested the relevance of cross‐taxon congruence patterns to predict these surrogacy patterns. We determined congruence between taxonomic groups by conducting a correlation analysis of dissimilarity values between pairs of sites. We then evaluated how well each taxonomic group represented the other groups in a marine reserve system selected by a greedy reserve‐selection algorithm relative to reserve systems selected by chance. No taxonomic group we examined was a reliable surrogate for the other groups such that site selection based on that group always represented other taxa significantly better than random selection of sites. Sites selected based on hard corals represented the other taxonomic groups in a reserve system worse than randomly selected sites. Although we found high cross‐taxon congruence between fishes and corals and between corals and mollusks, for some regions cross‐taxon congruence was not always a reliable indicator of the ability of one taxonomic group to efficiently represent another in a reserve system. We concluded that in Indo‐Pacific coral reef ecosystems one can only be sure that a target taxon is efficiently represented in a reserve system when data on that taxon are used to select a reserve system.

A theory for optimal monitoring of marine reserves - Leah R. Gerber; Maria Beger; Michael A. McCarthy; Hugh P. Possingham (Ecology Letters, 2005)
Monitoring of marine reserves has traditionally focused on the task of rejecting the null hypothesis that marine reserves have no impact on the population and community structure of harvested populations. We consider the role of monitoring of marine reserves to gain information needed for management decisions. In particular we use a decision theoretic framework to answer the question: how long should we monitor the recovery of an over‐fished stock to determine the fraction of that stock to reserve? This exposes a natural tension between the cost (in terms of time and money) of additional monitoring, and the benefit of more accurately parameterizing a population model for the stock, that in turn leads to a better decision about the optimal size for the reserve with respect to harvesting. We found that the optimal monitoring time frame is rarely more than 5 years. A higher economic discount rate decreased the optimal monitoring time frame, making the expected benefit of more certainty about parameters in the system negligible compared with the expected gain from earlier exploitation.

A Framework of Lessons Learned from Community-Based Marine Reserves and Its Effectiveness in Guiding a New Coastal Management Initiative in the Philippines - Maria Beger; Alastair R. Harborne; Terence P. Dacles; Jean-Luc Solandt; Gerardo L. Ledesma (Environmental Management, 2004)